Proximal Tibial Epiphysis Fracture in a 13-Year-Old Male Athlete - Ioannis M. Stavrakakis; Pavlos E. Katsoulis; Maria S. Katsafarou (Case Reports in Orthopedics)
Fractures of the proximal epiphysis of the tibia are rare, representing 0.5 to 3.0% of all epiphyseal injuries. These injuries can damage the popliteal vessels and their bifurcation, affecting the blood supply of the lower limb, as well as the nerves below the knee. Epiphyseal growth arrest is also a potential complication, leading to various angular deformities. We present a case of a 13-year-old male athlete with a posteriorly displaced Salter-Harris type II fracture of the proximal epiphysis of the left tibia who was treated conservatively with closed reduction and cast immobilization.